(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The primary aim of this study is to investigate the anatomical and functional alterations in the cardiovascular system of children following recovery from COVID-19 infection. The research seeks to identify subclinical myocardial injury, endothelial dysfunction, and autonomic imbalance that may develop as post-infectious sequelae. By comparing echocardiographic, electrocardiographic, and biochemical parameters between post-COVID-19 pediatric patients and healthy controls, the study aims to determine the extent and persistence of cardiovascular impairment. Furthermore, the study intends to establish correlations between laboratory markers of inflammation and cardiac function indices in order to elucidate potential mechanisms of myocardial and vascular damage.